A 14‐year‐old with 4 month history of a pen lid embedded in his tongue. (15th April 2014) - Gill, V.; Kerr, R.
Abstract: A patient presented with an unusual history of trauma to his tongue, for which he attended the emergency department. An infected, foreign body was embedded in his tongue from an injury sustained 4 months earlier. Foreign bodies in the tongue are rare; however, this case highlights the need for a thorough history and examination to avoid incorrect diagnosis.